Base of tongue neuroendocrine carcinoma: A case report. (June 2022) - Paquin, Rebecca; Gill, Brittany; Martin, Elizabeth; Byrd, J. Kenneth
Abstract: Neuroendocrine tumors are rare entities in the head and neck and an even more rare entity in the tongue. In this case report, we describe a calcified neuroendocrine tumor of the base of tongue that was presumed to be benign and was electively excised with pathology demonstrating low-grade carcinoma with focal neuroendocrine features and extensive ossification. We then discuss the histopathology and management.